Resveratrol, through NF-Y/p53/Sin3/HDAC1 complex phosphorylation, inhibits estrogen receptor α gene expression via p38(MAPK)/CK2 signaling in human breast cancer cells - De Amicis, Francesca (Federation of American Societies for Experimental Biology, 2011)
Agents to counteract acquired resistance to hormonal therapy for breast cancer would substantially enhance the long-term benefits of hormonal therapy. In the present study, we demonstrate how resveratrol (Res) inhibits human breast cancer cell proliferation, including MCF-7 tamoxifen-resistant cells (IC(50) values for viability were in the 30–45 μM range). We show that Res, through p38(MAPK) phosphorylation, causes induction of p53, which recruits at the estrogen receptor α (ERα) proximal promoter, leading to an inhibition of ERα expression in terms of mRNA and protein content. These events appear specifically p53 dependent, since they are drastically abrogated with p53-targeting siRNA. Coimmunoprecipitation assay showed specific interaction between p53, the Sin3A corepressor, and histone deacetylase 1 (HDAC1), which was phosphorylated. The enhancement of the tripartite complex p53/Sin3A/HDAC1, together with NF-Y on Res treatment, was confirmed by chromatin immunoprecipitation analyses, with a concomitant release of Sp1 and RNA polymerase II, thereby inhibiting the cell transcriptional machinery. The persistence of such effects in MCF-7 tamoxifen-resistant cells at a higher extent than parental MCF-7 cells addresses how Res may be considered a useful pharmacological tool to be exploited in the adjuvant settings for treatment of breast cancer developing hormonal resistance.—De Amicis, F., Giordano, F., Vivacqua, A., Pellegrino, M., Panno, M. L., Tramontano, D., Fuqua, S. A. W., Andò, S. Resveratrol, through NF-Y/p53/Sin3/HDAC1 complex phosphorylation, inhibits estrogen receptor α gene expression via p38(MAPK)/CK2 signaling in human breast cancer cells.